Characteristics of patients contacting a center for undiagnosed and rare diseases. Issue 1 (December 2016) - Mueller, Tobias; Jerrentrup, Andreas; Bauer, Max; Fritsch, Hans; Schaefer, Juergen
Abstract Background Little is known about the characteristics of patients seeking help from dedicated centers for undiagnosed and rare diseases. However, information about their demographics, symptoms, prior diagnoses and medical specialty is crucial to optimize these centers' processes and infrastructure. Methods Using a questionnaire, structured information from 522 adult patients contacting a center for undiagnosed and rare diseases was obtained. The information included basic sociodemographic data (age, gender, insurance status), previous hospital admissions, primary symptoms of complaint and previously determined diagnosis. Results The majority of patients completing the questionnaire were female, 300 (57 %) vs. 222 men (43 %). The median age was 52 years (range 18–92). More than half, 309 (59 %), of our patients had never been admitted to a university hospital. Common diagnoses included other soft tissue disorders, not classified elsewhere (ICD M79, n = 63, 15.3 %), somatoform disorders (ICD F45, n = 51, 12.3 %) and other polyneuropathies (ICD G62, n =36, 8.7 %). The most frequent symptoms were general weakness (n = 180, 36.6 %) followed by arthralgia (n = 124, 25.2 %) and abdominal discomfort (n = 113, 23.0 %). The majority of patients had either internal medicine (81.3 %) and/or neurologic (37.6 %) health problems. Conclusions Pain-associated diagnoses and the typical "unexplained" medical conditions (chronic fatigue syndrome, fibromyalgia, irritable bowel syndrome) are frequent among people contacting a center dedicated to undiagnosed diseases. The chief symptoms are mostly unspecific. An interdisciplinary organizational approach involving mainly internal medicine, neurology and psychiatry/psychosomatic care is needed.